Kaleidoscopic ethnicity : international migration and the reconstruction of community identities in India - Kurien, Prema A. (Oxford University Press, 2002)
"Based on ethnographic research in three ethno-religious communities (Ezhava Hindu, Mappila Muslim, and Syrian Christian) in Kerala, India, which sent large numbers of workers to the Middle East for temporary jobs, Kaleidoscopic Ethnicity explores the factors responsible for the striking differences in the groups' patterns of migration and migration-induced social change. Most broadly, Prema Kurien seeks to understand what ethnicity is and how it affects people's activities and decisions.